Night-time animals - Royston, Angela (New York : Aladdin Books, 1992)
Text and photographs describe some animals who are active at night, such as foxes, bats, owls, and fieldmice.
"A Dorling Kindersley book."
Keywords: Nocturnal animals -- Juvenile literature